Experiences of Postgraduate Doctoral Students’ Supervision Through Distance Education: A Case of Oshana Region, Namibia - Shapaka, Rehabeam (Papanda Publishier, 2025)
This article delves into postgraduate doctoral students learning experiences at doctoral supervision aiming to investigate postgraduate doctoral students learning experiences at doctoral supervision at distance education in Oshana Region in Namibia. Qualitative case study research design, which emanates from constructivist worldview, was employed to explore postgraduate doctoral students learning experiences at doctoral supervision at distance education in Oshana Region in Namibia. Interview schedules, field notes and open-ended questionnaire were used to collect data. Criterion purposeful sampling technique was used to choose six doctoral students who finished doctorate studies at distance education. Typological analysis, thematic analysis, content analysis and Atlas.ti were used to analyse data. Findings have established that a close relationship and effective communication in postgraduate doctoral student supervision constitutes practices which have effects on postgraduate student supervision which affect their performance which result in positive and negative postgraduate student outcomes. Postgraduate doctoral student should use supervision practice to improve, enhance their performance. Postgraduate doctoral student should study and learn the application of postgraduate doctoral supervision practice; apply them to optimise success and enhance teaching and learning that result on postgraduate doctoral student outcomes. The type of relationship, and communication, academic and personal concern and interest, mode of supervision as well as challenges faced by postgraduate doctoral student have effect on postgraduate doctoral student supervision.